Mudharabah Financing Dispute Resolution in Sharia Banking - Khairunnisak, Zaisika; Purba, Hasyim; Maharany Barus, Utary; Aprilyana, Idha (KnE Social Sciences, 2024)
Indonesia adopted the Sharia Law System. The implementation of the adoption of the Sharia Law System, the legal fact, has resulted in the development of Sharia banking business practices in Indonesia. In carrying out Sharia banking business practices, Sharia banks can distribute funds to customers receiving facilities in the form of mudharabah financing. In the implementation of the mudharabah contract, disputes can occur, which of course must be resolved. This research discusses mudharabah financing by Sharia banks to the customers who receive facilities, which in practice does not rule out the possibilities between Sharia banks and customers receiving facilities, which of course must be resolved. In this regard, this research is focused on examining the legal certainty of mudharabah financing dispute resolution in Sharia banking. This research type used is normative. The method used in this research is a normative juridical research method. This research is a desscriptive analysis, using various types of data in legal research. The study’s findings suggest that in the absence of a dispute resolution provision in the mudarabah contract, disputes were resolved in religious tribunals. If there is a clause, nonetheless, its application must not go against Shariah law. In the event of any non-compliance, the Central Bank of Indonesia (Bank Indonesia) will impose administrative sanctions on Shariah banks. Keywords: dispute, financing, Sharia